The Correlation of Clinicopathological Characteristics in Clear Cell Renal Cell Carcinoma (ccRCC) with Immunohistochemical Expression of Light Chain 3 B (LC3-B) - Alferraly, T. Ibnu; Chrestella, Jessy; l, Lidya Imelda; Lukito, Joko S.; Rezeki, Dewi Sri (Majalah Patologi Indonesia, 2025)
Background: Clear cell renal cell carcinoma (ccRCC) is the most common histological subtype in RCTs. This tumor is very aggressive and is often diagnosed at an advanced stage. LC3-B is a specific autophagy marker that plays a role in ccRCC. Research regarding the relationship between clinicopathological characteristics of ccRCC and LC3-B expression is still very limited and controversial. Objective: To assess the relationship between clinicopathological characteristics of ccRCC and LC3-B immunohistochemical expression. Materials and methods: This study used 22 slide samples/paraffin blocks of ccRCC cases that had been diagnosed histopathologically at the Anatomic Pathology Unit of H. Adam Malik General Hospital, Medan from January 2017 to April 2023. All clinicopathological data was taken from medical records/pathology archives. LC3-B expression was assessed in the cytoplasm of tumor cells with assessment semiquantitatively based on the multiplication of intensity and percentage of expressed tumor cells. Statistical analysis was carried out using Fischer's Exact and Kruskal Wallis tests. Results: Among the 22 ccRCC samples, weak expression of LC3-B was found in the age group ≤60 years, male gender, tumor size >10 cm, positive LVI, negative PNI, grade IV, severe stromal TILs, mild intratumoral TILs and low budding in intratumoral budding tumors. Fischer's Exact and Kruskal Wallis statistical tests showed that there was no significant relationship between gender, tumor size, LVI, PNI, ISUP grading, TILs and peritumoral tumor budding with LC3-B expression. Conclusion: There was no significant relationship between clinicopathological characteristics of ccRCC with LC3-B expression (The Null Hypothesis is accepted (H0 ρ=0)). Key words: clinicopathology, ccRCC, LC3-B